2011
DOI: 10.1074/jbc.m110.188565
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Action of Casein Kinase 1 and Calcineurin in Nucleo-cytoplasmic Shuttling of Mammalian Translation Initiation Factor eIF6

Abstract: Eukaryotic initiation factor 6 (eIF6), a highly conserved protein from yeast to mammals, is essential for 60 S ribosome biogenesis and assembly. Both yeast and mammalian eIF6 are phosphorylated at Ser-174 and Ser-175 by the nuclear isoform of casein kinase 1 (CK1). The molecular basis of eIF6 phosphorylation, however, remains elusive. In the present work, we show that subcellular distribution of eIF6 in the nuclei and the cytoplasm of mammalian cells is mediated by dephosphorylation and phosphorylation, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 37 publications
2
37
1
1
Order By: Relevance
“…It has been reported that p65 can be phosphorylated at Ser 468 and Ser 536 and these modifications related to the activity of p65 (20)(21)(22), and it is known that CK1 family members regulate the biological process by phosphorylating their target molecules (10)(11)(12)(13)(14). We therefore examined whether CK1g1 phosphorylates p65.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that p65 can be phosphorylated at Ser 468 and Ser 536 and these modifications related to the activity of p65 (20)(21)(22), and it is known that CK1 family members regulate the biological process by phosphorylating their target molecules (10)(11)(12)(13)(14). We therefore examined whether CK1g1 phosphorylates p65.…”
Section: Resultsmentioning
confidence: 99%
“…The casein kinase 1 (CK1) is a family of Ser/Thr protein kinases that functions as regulator in signal transduction of eukaryotic cells (10). Studies have shown that CK1 family members were involved in many biological processes, such as the regulation of Wnt signaling (11), circadian rhythm (12), nucleus-cytoplasm shuttling of transcriptional factors (13), mitosis, and DNA repair (14). In this study, we demonstrated that CK1g1 phosphorylates NF-kB subunit p65 and promotes its ubiquitin-mediated degradation and therefore inhibits the RIG-I signaling pathway.…”
Section: R Etinoic Acid-inducible Gene I (Rig-i)-mediated Signalingmentioning
confidence: 99%
“…Hrr25 belongs to the casein kinase 1 (CK1) family of protein kinases and is the yeast ortholog of the mammalian CK1d enzyme (DeMaggio et al 1992). The Hrr25/CK1d proteins have conserved roles in ribosome maturation, vesicle trafficking, DNA repair, and chromosome segregation during meiosis (Hoekstra et al 1991;Petronczki et al 2006;Schafer et al 2006;Ray et al 2008;Grozav et al 2009;Biswas et al 2011;Isoda et al 2011;Lord et al 2011). We report here that this critical regulator of cell proliferation is efficiently recruited to P-bodies in both yeast and mammalian cells under all conditions examined.…”
mentioning
confidence: 88%
“…Notably, CK1 has also been linked to 60S biogenesis because it has been shown that mammalian eIF6, the ortholog of yeast Tif6, is phosphorylated by CK1 (Basu et al, 2001), which leads to changes in the subcellular distribution of eIF6 (Basu et al, 2001;Biswas et al, 2011). However, it remains unclear how this phosphorylation affects nuclear export or cytoplasmic maturation of 60S precursors.…”
Section: Introductionmentioning
confidence: 99%